Plasma Fibulin-3 as a Potential Biomarker for Patients with Asbestos-Related Diseases in the Han Population. (22nd October 2017) - Jiang, Zhaoqiang; Ying, Shibo; Shen, Wei; He, Xianglei; Chen, Junqiang; Xia, Hailing; Yu, Min; Xiao, Yun; Feng, Lingfang; Zhu, Lijin; Ju, Li; Guo, Xinnian; et al.
Abstract : Fibulin-3 has been reported as a potential biomarker for mesothelioma. However, little is known about the diagnostic efficacies of fibulin-3 for asbestos-related diseases (ARDs) in China. This study was to investigate the utility of fibulin-3 for asbestos exposure and ARDs. A total of 430 subjects were recruited from Southeast China, including healthy individuals, asbestos-exposed (AE) individuals, and patients with pleural plaques (PP), asbestosis, and malignant pleural mesothelioma (MPM). Plasma fibulin-3 was measured using the enzyme-linked immunosorbent assay. Linear regression analyses were applied to explore the influencing factors of fibulin-3. Receiver operating characteristic curves were used to determine the cutoff values. The median fibulin-3 level of subjects in the mesothelioma group was higher than that in other groups. Subjects in the asbestosis group had higher median fibulin-3 level than those in the control group. A higher fibulin-3 level was found in the group with ≥10 years of asbestos exposure as compared with control groups. The AUCs of fibulin-3 for distinguishing MPM subjects from control, AE, PP, and asbestosis subjects were 0.92, 0.88, 0.90, and 0.81, respectively. Our study provided evidence that fibulin-3 could be a potential biomarker for the early screening of MPM, but not of other nonmalignant ARDs in Chinese populations.